La racionalización técnica de la Contratación: Título II, del Libro III, de la Ley 30/2007, de 30 de octubre, de Contratos del Sector Público (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2010)
This report aims to bring as much light as possible on some of the techniques governed by the new Public Procurement Act, more specifically the technical rationalization of contracts. The Act dedicates an entire chapter to rationalizing the procurement procedures through general guidelines, dynamic systems; public works centralized purchasing units, services and supplies, all of these according to EU regulation. Though these motions are not new in our domestic Law, the way they have been regulated gives them an appearance of novelty. This is due to the fact that theAct has taken over almost literally, the contents of the EU Directive 2004/28, but with a high degree of flexibility, which has brought about a tangle of confuse legal motions and vague expressions with no clear interpretation. These systems are designed to speed up and to rationalize the procedures for all identical or similar procurement contracts. But as this aim requires on intensives use of the new technologies all administrative bodies, which has not yet been achieved in Spain, the Act misses therefore its aim.I have consistently tried to follow the same order with all systems: their origin then their evolution, for once we know these technologies and their use in Spain from the beginning, we are in a better position to understand their definition (which is not provided by de Act) their implementation, their procedure and finally their awarding with their respective peculiar features.